2015
DOI: 10.5014/ajot.2015.017954
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Dyspraxia and the Play Skills of Children With Autism

Abstract: Praxis problems in children with ASD greatly affect their successful participation in play and leisure activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 37 publications
0
18
0
9
Order By: Relevance
“…[20,21] Studies have shown that sensory and motor development differences may cause motor planning difficulty during daily living activities, affecting quality of life of children with ASD from early stage of life. [14][15][16][17][18][23][24][25][26] The present study indicated that autistic children without history of trauma had better scores in 9-Hole Peg Test and Jebsen Hand Function Test. It has been determined that autistic children with trauma history had greater limitation in fine motor skills.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[20,21] Studies have shown that sensory and motor development differences may cause motor planning difficulty during daily living activities, affecting quality of life of children with ASD from early stage of life. [14][15][16][17][18][23][24][25][26] The present study indicated that autistic children without history of trauma had better scores in 9-Hole Peg Test and Jebsen Hand Function Test. It has been determined that autistic children with trauma history had greater limitation in fine motor skills.…”
Section: Discussionmentioning
confidence: 98%
“…Manual Form Perception and Localization of Tactile Stimuli subtests specifically test somatosensory perception, while the other tests include assessment of praxis. [13][14][15][16][17] The 9-Hole Peg Test is a brief, standardized, quantitative test of upper extremity function. Both dominant and non-dominant hands are tested twice.…”
Section: Somatosensory Subtests Of Sensory Integration and Praxismentioning
confidence: 99%
“…Os déficits de Integração Sensorial afetam as habilidades de performance motora e funcional e podem afetar a forma como as crianças se comportam, incluindo as habilidades de aprender, organizar e manter um nível de atenção apropriado para as atividades (Mulligan, 1996). De acordo com Bodison (2015), estudos sugerem que déficits na praxia também limitam a participação da criança no ambiente e, podem se relacionar com os déficits na socialização.…”
Section: Praxia E Dispraxiaunclassified
“…A reatividade sensorial é um dos muitos problemas em Integração Sensorial (IS) relacionado a padrões de funcionamento conhecidos que afetam crianças que tem problemas e desafios de aprendizagem e de comportamentos 2015). Reatividade sensorial está relacionada à maneira como a criança reage a um estímulo sensorial, ou seja, quando a criança tem uma dificuldade em ter uma resposta apropriada em relação à intensidade, natureza ou grau do estímulo sensorial (Serrano, 2016).…”
Section: Praxia E Dispraxiaunclassified
See 1 more Smart Citation